A Review of District Heating Systems: Modeling and Optimization - Talebi, Behrang; Mirzaei, Parham A.; Bastani, Arash; Haghighat, Fariborz (Frontiers in Built Environment, 2016)
The ever-increasing demand for heating in different sectors, along with more preventative regulations on greenhouse emissions, has forced different countries to seek new alternative to heat buildings such as District Heating System (DHS). Although the traces of district heating systems can be observed over the centuries, it was not widely implemented until last two decades when the DHS become a method to design more green and energy efficient way for heating buildings. This paper tries to review the state of the art in modeling different components of the district heating systems and state the advantages as well as limitation of each method. Also, different methods used for the optimization of the DHSs have been reviewed.